Impact of Culture in Multicultural Groups: Cross Analysis between China and India - Chung, Jae; Chadwick, Leslie; Ghafoor, Shahzad; Khan, Uzair Farooq (Journal of Asian Scientific Research, 2011)
With the increasing trend of globalization, the impact of globalization has lead to a fast changing environment the boundaries for business is diminishing day by day so is the movement of people between different countries and cultures. The requirements of multinational organizations like expansion plans in international market has continuingly increased the need to understand the cultural dimensions of different countries to achieve better results. Therefore the companies are required to understand a national culture’s impact on areas like communication in multicultural teams in different countries which has a high degree of effect on team performance. So our research question revolves around this topic as “How does culture influence communication in multi cultural teams”. This paper makes an attempt to investigate the influence of national cultures on communication in project teams in China and India by focusing on construction industry based on a number of factors including Hofstede’s (1980) cultural dimensional framework. The researchers intend to explore the cultural factors having major impact on communication in multicultural project teams of both countries. Throughout our research and study, useful lessons on national cultures impact on communication can be drawn for multicultural project team in China and India. It can provide a better insight for the project teams to have concern for and understand why people from different countries and cultures react or respond to various situations in a different manner, giving high emphasis to communication process.